The effect of special exercises on some Biomotor abilities and the indicator of serving accuracy and spiking for volleyball players - Farhan, B. A. (International Journal of Yogic, Human Movement and Sports Sciences, 2023)
The importance of the research lies in the preparation of special exercises for the development of some important biomotor abilities and the indicator of accuracy of serving and spiking, which has the effect of raising the technical level of volleyball players. While the research problem was that the ball player suffers from a weakness in the biomotor abilities, which has an important impact on the indicator of the accuracy of the serving and spiking of the volleyball players. This study aimed to prepare special exercises for the development of some of the biomotor abilities and the indicator of accuracy of serving and spiking of volleyball players, and then to identify their impact, and I assume that there is a positive effect of special exercises according to the level of difficulty, a positive impact on the development of some of the biomotor abilities and the indicator of accuracy of serving and spiking of players volleyball. The researcher used the experimental approach with two experimental and control groups due to its suitability to the nature of the research problem, as the research community included a group of volleyball players in the Project Sports Club at the ages of 15-17 years for the season 2022, whose number is (20) players, and then they were randomly divided into two experimental and control groups by (8) players for each group, and then do the pre-test, the researcher started with one starting line to implement the special exercises set along the duration of the training curriculum, and after applying the exercises, the researcher did a post-test and obtained data, after which these data were treated statistically, and then information was obtained on which conclusions were built, the most important of which is that special exercises have an effective role in developing biomotor abilities research is significantly under the experimental group. The development of biomotor abilities had a tangible impact on the development of the indicator of accuracy of serving and spiking for volleyball players, and then the researcher recommended the need to design training programs determined in the light of the abilities of the players and higher in order to ensure the remarkable development and the development of biomotor abilities had a tangible impact in developing the indicator of accuracy of serving and spiking of volleyball players.